The Impact of Implementing Digital Transformation and Information Technology on Mydepo Application Towards Operation Smoothness at Pelni Logistics - Ratu Nadiyah Herliaty; Siti Raidah; Aswanti Setyawati; Azmieti Kurnia Sinta (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Pelni Logistic has adapted with a digital application namely MyDepo. The use of the MyDepo application in Pelni Logistics operations facilitate reporting and ship route tracking processes and improve the accuracy of the data needed by the company, replacing the previously time-consuming and labor-intensive manual methods. Therefore, this research explores the impact of digital technology development on the logistics industry, especially digital transformation and information technology on operation smoothness. This research using quantitative methods and collecting data through questionnaire surveys for analysis and the method of sampling is simple regression. Data is processed using SPSS tools, and the sample consists of 50 employees from Pelni Logistic offices in Jakarta, Surabaya, and Bitung. The findings of this research show that all hypotheses have positive and significant effects, demonstrating the role of digitalization in enhancing operational performance.